Pemberdayaan Perempuan melalui Refleksi Diri dan Coaching di Lingkungan Profesional: Pengabdian - Nurmayanti Zain (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program was conducted to commemorate Kartini Day through the initiative Journey to The Authentic & Empowered Self, held on April 29, 2025, at the Fiber Room, Telkom Regional 5 Plaza Telkom Indonesia, Makassar. The program targeted professional women of the Srikandi Telkom Group in Eastern Indonesia (KTI), with a focus on enhancing self-awareness, strengthening peer support (She for She), and promoting role transformation through coaching and reflection on Kartini’s values. Activities included reflective presentations, interactive discussions, self-awareness exercises, and group coaching based on emotional support. Results showed increased participant awareness of authentic self-values in social-emotional interactions. Around 85% of participants reported better recognition of their personal needs. They also expressed strong interest in empathy-based leadership and proposed continuity of such programs. This initiative strengthened individual capacity and encouraged the development of a supportive and inclusive work culture. It serves as a model of psychosocial, transformative community engagement for professional women.